Mean Orbital Elements for Geosynchronous Orbit - II - Orbital inclination, longitude of ascending node, mean longitude - Kyu-Hong Choi (Journal of Astronomy and Space Sciences, 1990)
The osculating orbital elements include the mean, secular, long period, and short period terms. The iterative algorithm used for conversion of osculating orbital elements to mean orbital elements is described. The mean orbital elements of Wc, Ws, and L are obtained.